2014
DOI: 10.1080/02786826.2014.924614
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Particle Collection Efficiency of Holey Carbon Film-Coated TEM Grids

Abstract: A simple sampling method to collect aerosol particles for transmission electron microscope (TEM) analysis was developed by R'mili and others in 2013. The method involves passing air through a holey carbon film-coated copper mesh TEM grid (holey carbon grid) and sampling particles by filtration. In this study, we proposed a modified calculation method to represent the collection efficiencies of holey carbon grids, taking into consideration the porosity of the copper mesh. We then evaluated the particle collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Actually, the moderate inertia effect may explain the difference in the experimental surface collection efficiencies between 30 nm PSL and Ag particles shown in Figure 5. The value of Stk for the 30 nm Ag particle under the test conditions in Figure 5 seemed to be moderate (Stk D 0.02; from Equation (18) of Ogura et al 2014), while the value of Stk for the 30 nm PSL particle seemed to be low (Stk D 0.002). For this reason, it is considered that the 30 nm Ag particle was affected by the moderate inertia effect while the 30 nm PSL particle was almost unaffected.…”
Section: Errors and Uncertainty In Theoretical Collection Efficienciesmentioning
confidence: 90%
See 2 more Smart Citations
“…Actually, the moderate inertia effect may explain the difference in the experimental surface collection efficiencies between 30 nm PSL and Ag particles shown in Figure 5. The value of Stk for the 30 nm Ag particle under the test conditions in Figure 5 seemed to be moderate (Stk D 0.02; from Equation (18) of Ogura et al 2014), while the value of Stk for the 30 nm PSL particle seemed to be low (Stk D 0.002). For this reason, it is considered that the 30 nm Ag particle was affected by the moderate inertia effect while the 30 nm PSL particle was almost unaffected.…”
Section: Errors and Uncertainty In Theoretical Collection Efficienciesmentioning
confidence: 90%
“…The E I and E D can be calculated using the popular models proposed by Pich (1964) and Manton (1979), respectively. The details of those equations were summarized in Ogura et al (2014). For calculating E R , various expressions have been proposed (Spurny et al 1969;Smith et al 1976;John et al 1978;Marre and Palmeri 2001).…”
Section: Theoretical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The particulate matter sampling was performed directly from the aerosol flow by passing a sample flow of 0.5 L min -1 through the grid -a pump coupled with a critical orifice was used to generate and control the aerosol flow. The main collection mechanism for particulate matter was diffusion to the grid surface (Ogura et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, a low-cost, portable, and easy used instrument, TEM grid-equipped Mini Particle Sampler, was developed by Institute National de l'Environnement Industrial et des Risques (INERIS) and commercialized by the company Ecomesure, , as shown in Fig. 1 [15][16][17]. Researches on powder structure characterization [18][19] and nanomaterial exposure assessment [20][21][22][23][24] have validated the applicability of the MPS.…”
Section: Introductionmentioning
confidence: 99%